The word and the world : Indiaʾs contribution to the study of language - Matilal, Bimal Krishna (Oxford University Press, 1990)
In this monograph Professor B.K.Matilal studies what is today called "philosophy of language" on the basis of materials drawn exclusively from the works of classical Indian philosophers. He provides not simply an exposition, but also an analysis of classical theories, allowing the texts to speak for themselves and avoiding any comparisons with modern theories. The book is divided into two parts: one presents a survey of the general issues and problems; the other selects several special topics for study, such as sphota theory, the word as a unit of a sentence, the problem of translation, and an elaboration of Bhatrhari's view of cognition.